DURING THE WORK ON THE CONCEPTS OF LITERARY THEORY. COMPUTER USE - Peri Pashayeva (European Research Materials, 2023)
Literary theory materials are taught in the form of separate concepts in connection with literary-artistic materials in secondary schools. As shown above, the need for grouping in terms of computer use has emerged, theoretical concepts are also combined in one section, and it is considered appropriate to talk about the possibilities of using computers in the process of teaching them to students. The teaching of literary theory materials (of course, in the form of individual concepts) in the literature classes of general education schools is very important and requires special care and attention. The need to teach theoretical concepts comes from the fact that this knowledge, given in the form of concepts, is generally the basis of students’ literary knowledge. However, it should also be said that the weakest aspect of literature teaching in general education schools, if it is possible to say, is the teaching of theoretical materials. It must be admitted that mastering literary-theoretical concepts is more difficult than mastering literary-historical materials. This difficulty is clearly observed in the school experience. Therefore, the teaching of theoretical concepts in literature classes requires the teacher to have deep theoretical knowledge as well as pedagogical skills. In this work, the teacher has to use different methods and tools.